A study of working conditions in the shops of non-ferrous casting - A. M. Lazarenkov (Литьë и металлургия, 2020)
The results of the study of working conditions of workers in non-ferrous casting shops are presented. It is shown that the main production factors of working conditions are noise, vibration, dust, gas, air temperature, the intensity of infrared (thermal) radiation, the severity and intensity of the labor process. The results of the research have shown that all workplaces have exceeded the permissible values for noise, dust content in the air of the working environment, the intensity of infrared (thermal) radiation and air temperature.It is noted that the work performed due to the severity and intensity of the labor process can negatively affect the health of employees.